Acute Effect Of Ultrasound Therapy And Active Stretching In Cases Of Calcaneus Spur - Nahdliyyah, Ade Irma; Wulandari, Tiara (Universitas Pekalongan, 2024)
Calcaneus spur is a cartilage disease that occurs in the heel area so it can affect the sufferer's activities. The symptoms felt are pain, limited range of joint movement, and decreased muscle strength. The physiotherapy examination carried out in this case included pain examination with the Visual Analogue Scale, range of motion with a goniometer, muscle strength with Manual Muscle Testing and functional activity with the Foot Ankle Disability Index. The modalities used are ultrasound (US) therapy and exercise therapy. The aim of this study was to determine the effect of physiotherapy management on the condition of left calcaneal spurs using Ultrasound (US) and Exercise Therapy modalities. The research was conducted at the Kajen General Hospital, Pekalongan Regency with a descriptive analytical research design. The research subjects were patients with left calcaneus spur conditions with Ultrasound (US) and Exercise Therapy modalities. Data collection and analysis methods use the autoanamnesis method, as well as pain examination instruments, examination of joint range of motion, and functional activities. The results of the study were 4 treatments: (1) pain decreased (2) there was an increase in range of motion (3) there was no increase in muscle strength. (4) there is an increase in daily functional activities. The research concludes that physiotherapy intervention using Ultrasound (US) and Exercise Therapy can reduce the problems caused by the condition of the left calcaneus spur, namely reducing pain, increasing joint range of motion, and increasing functional activity.